Role of VDR in 1α,25-dihydroxyvitamin D3-dependent non-genomic activation of MAPKs, Src and Akt in skeletal muscle cells - Buitrago, Claudia Graciela (2013)
1α,25-dihydroxyvitamin D3 [1,25D] is recognized as a steroid hormone that rapidly elicits intracellular signals in various tissues. In skeletal myoblasts, we have previously demonstrated that one of the 1,25Dinduced non-genomic effects is the upstream stimulation of MAPKs through Src activation. In this work, the data obtained suggest that the classical receptor of vitamin D (VDR) participates in non-transcriptional actions of 1,25D. We significantly reduced VDR expression by infection of C2C12 murine myoblasts with lentiviral particles containing the pLKO-1 plasmid with information to express a shRNA against mouse VDR. In these cells (C2C12-shVDR), Western blot analyses show that 1,25D-induced p38 MAPK activation and Src tyr416 phosphorylation were abolished. In addition, 1,25D-dependent activity of ERK1/2 was diminished in cells lacking VDR but to a lesser extent (∼-60%). Phosphorylation of Akt by 1,25D, recently demonstrated in C2C12 cells, in the present work also appeared to be partially dependent on VDR expression (∼50% in C2C12-shVDR cells). Our results indicate that VDR is involved in 1,25D-induced rapid events related to survival/proliferation responses in skeletal muscle cells, providing relevant information on the mechanism of initiation of the non-genomic hormone signal. The participation of a VDR-independent non-genomic mechanism of action should also be taken into consideration.